2015
DOI: 10.1016/j.jconrel.2015.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial delivery of Coenzyme Q10 via systemic administration using a MITO-Porter prevents ischemia/reperfusion injury in the mouse liver

Abstract: We herein report on a mitochondrial therapeutic effect based on the delivery of coenzyme Q10 (CoQ10), an anti-oxidant, to in vivo mitochondria using a MITO-Porter, a liposome-based mitochondrial delivery system that functions via membrane fusion. To evaluate the effects, we used a mouse liver ischemia/reperfusion injury (I/R injury) model, in which mitochondrial reactive oxygen species are overexpressed. We packaged CoQ10 in the lipid phase of a MITO-Porter and optimized the mitochondrial fusogenic activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…PLGA-CoQ 10 NPs of <100 nm were successfully prepared by an emulsion-diffusion-evaporation method, which demonstrated enhanced oral bioavailability and anti-inflammatory activity compared to free CoQ 10 (Figure 11) (162). Recently, Yamada et al reported Co Q 10 delivery using MITO-Porter, a liposomal delivery system, to target mitochondria for preventing IR injury (163). The CoQ 10 -MITO-Porter was intravenously injected in the hepatic IR injury mice model.…”
Section: Mitochondrial Targets For Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…PLGA-CoQ 10 NPs of <100 nm were successfully prepared by an emulsion-diffusion-evaporation method, which demonstrated enhanced oral bioavailability and anti-inflammatory activity compared to free CoQ 10 (Figure 11) (162). Recently, Yamada et al reported Co Q 10 delivery using MITO-Porter, a liposomal delivery system, to target mitochondria for preventing IR injury (163). The CoQ 10 -MITO-Porter was intravenously injected in the hepatic IR injury mice model.…”
Section: Mitochondrial Targets For Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…14) Lipid, CoQ 10 and DMG-PEG2000 stock solutions were prepared in ethanol and stored at −20°C until used. A 100% (v/v) EtOH solution containing 2.75 mM lipids [DOPE/SM/DMG-PEG2000 (9/2/0.33, molar ratio)] was prepared.…”
Section: Preparation Of Coq 10 -Liposomes By Lipid Film Hydration Methodsmentioning
confidence: 99%
“…14) Since liposomes that are prepared using different methods can result in significant differences in drug encapsulation efficiency and the physiochemical characteristics of the carrier, liposomes prepared using the three methods as shown in Fig. 1 were compared.…”
Section: Preparation Of Coq 10 Encapsulating Liposomes and Their Physmentioning
confidence: 99%
See 2 more Smart Citations